Discovering grammar through corpus II - Ramírez Acosta, Jimmy (2022)
The book Discovering Grammar Through Corpus II is intended to help students understand basic grammar topics through on an inductive approach. This book has been designed to be used with the Corpus of Contemporary American English COCA which is a growing 560-million-word Corpus that depicts language as it is used naturally. This book is organized into two content units that are made up by mini lessons. These units focus on the specific topics of: verb tenses, vocabulary, writing patterns and punctuation.